Harden Up! Analysing Soft News in New Zealand’s Prime-Time Television News Bulletins - Jones, Haley-Georgia (Auckland University of Technology, 2017)
New Zealand television news programming is an area of media research that has been widely explored in previous decades. Studies have determined that in the wake of deregulation in 1989, One Network News adopted a more informal and tabloidized news format, and heightened the dramatization and personalisation of the news bulletin. This change has not only been seen in news programmes, but in current affairs programmes as well. Measuring these changes is important as the news media’s most crucial function in an ideal democratic system is to inform and educate the public. If the news media is not fulfilling this role, then it stands to reason that this would significantly impact upon democracy itself. Yet, despite the need for ongoing critical analysis of the news media, prime-time news content in New Zealand has not been critically analysed since the 1990s. By focusing on 2015 news bulletins from One News and 3 News, this study updates existing New Zealand television news research. A content analysis with a sample size of two constructed weeks was used to determine what comprised One News and 3 News bulletins. The main objective was to analyse and compare the content of the competing channels’ bulletins, and to determine if One News had changed significantly in comparison to the One Network News findings from the 1990s. Not only were news bulletins measured for all non-news and news content, they were also analysed for the presence of hard and soft news stories. The study found that there was little difference between the One News and 3 News bulletins. It identified a large presence of non-news content (such as advertising and weather) compared to previous studies, and found that political news content has continued to decrease while tabloidized content has increased. Additionally, soft news—especially soft sports news—dominated both the One News and 3 News bulletins, which reflects the changes in presentation and style identified by earlier research. The most profound finding of the study was the emergence of hybrid news items; whereby a traditionally hard news story had been given a soft news treatment by stripping it of political or societal context and providing only a personal or emotional focus. The large presence of soft news—combined with the emerging news hybridity—indicates that soft news approaches have become embedded in journalistic practices in television news. This raises serious concerns over the quality of information that is disseminated to the New Zealand public, and the effectiveness of the New Zealand television news media in facilitating a healthy public sphere.
Keywords: Content analysis; New Zealand; Television; News; One News; 3 News; TVNZ; Soft news; Hard news; Political economy; Broadcasting; Deregulation; Politics; Tabloid; Sport